Jackhammer Esophagus: From Manometric Diagnosis to Clinical Presentation. (3rd March 2019) - Clément, Marianne; Zhu, Wen Jing; Neshkova, Elissaveta; Bouin, Mickael
Abstract : Background . Jackhammer esophagus is a hypercontractile esophageal disorder recently brought to light with the advent of high resolution manometry (HRM). As little is known about its clinical presentation, the aim of this study was to identify the clinical characteristics associated with this new gastrointestinal motility disorder. Methods . A retrospective study was conducted on patients visiting the CHUM's Gastro-Intestinal Motility Center from January 2015 to December 2017. The HRM diagnoses were collated in a database along with age and sex of every individual. The latest Chicago classification (version 3.0) was used. Among all the patients subjected to HRM, those diagnosed with Jackhammer esophagus were included in the study. Patient charts were reviewed to collect relevant demographic and clinical data. Key Results . A total of 36 patients with Jackhammer esophagus were included (62± 13 years age, 89% females). Their main symptoms were dysphagia (72%), pyrosis (42%), retrosternal chest pain (36%), and epigastralgia (33%). Other manometric findings were hypertonia (22%) and/or inadequate relaxation (19%) of the lower esophageal sphincter. Among the 26 patients who had esogastroduodenoscopy, hiatal hernia was seen in 3 patients. Pathological gastroesophageal reflux was found in 4 of the 10 patients investigated by pH-monitoring. Conclusions and Inferences . Jackhammer esophagus represents 3% of the HRM diagnoses in this study, with a significant female preponderance. In more than two-thirds of cases, the clinical presentation of Jackhammer esophagus is dysphagia.